DESIGNING CONTEXTUAL MATHEMATICS LEARNING WORKSHEETS BASED ON NATURE AND LOCAL CULTURE FOR INDIGENOUS STUDENTS - Fredy Fredy; Mohamad Ilham; Andi Saparuddin Nur; Wa Ode Siti Hamsinah Day (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Mathematics is often perceived as difficult and abstract by students, especially when learning materials are not connected to their daily lives. This is particularly relevant for indigenous students, whose cultural and environmental contexts are rarely represented in conventional textbooks. This research developed contextual mathematics learning worksheets that integrate natural elements and local culture to support indigenous students’ numeracy and literacy in Merauke. The study employed a four-D development model: define, design, develop, and disseminate. The methodology involved field observations, curriculum analysis, expert validation, and classroom trials in selected elementary schools. The resulting learning material took the form of student worksheets featuring culturally relevant topics, such as calculating area and volume through local tools and traditional activities. Expert assessments rated the materials as highly appropriate in both content and media aspects. Furthermore, the implementation showed significant improvement in students' mathematical problem-solving abilities. The paired sample t-test indicated a statistically significant difference between pre-test and post-test scores. The normalized gain score of 0.28 placed the improvement in the medium category. These findings suggest that context- and culture-grounded learning materials can enhance the relevance and effectiveness of mathematics education for indigenous learners.